The companion guide to Venice - Honour, Hugh (Collins, 1965)
There are few pleasanter ways of passing a summer's evening than sitting over a cup of coffee, and perhaps a glass of Aurum, in the Piazza San Marco. It is especially agreeable on those nights when the Venetian city band thunders away at some throbbingly romantic piece... And all the while the younger inhabitants parade around the square, chattering, flirting, quarrelling and staring at their visitors with that same unwinking gaze that Venetians have turned on their guests for the past five centuries. The facade of San Marco closes the scene in a glitter of golden mosaic and a bubbling of cupolas, while the great thick red campanile stretches up into the warm mothy darkness of the summer sky. Hugh Honour, it is clear, knows Venice exceptionally well and catches the rhythms of the city's life with unerring skill. His guide, with its winning blend of evocative detail and precise information, spurs the reader to investigate Venice's wonders: Piazza San Marco is only the beginning of a journey into the heart of Venice and its history.